Gut Microbiota Modulates Interactions Between Polychlorinated Biphenyls and Bile Acid Homeostasis. (24th August 2018) - Cheng, Sunny Lihua; Li, Xueshu; Lehmler, Hans-Joachim; Phillips, Brian; Shen, Danny; Cui, Julia Yue
Abstract: The gut microbiome is increasingly recognized as a second genome that contributes to the health and diseases of the host. A major function of the gut microbiota is to convert primary bile acids (BAs) produced from cholesterol in the liver into secondary BAs that activate distinct host receptors to modulate xenobiotic metabolism and energy homeostasis. The goal of this study was to investigate to what extent oral exposure to an environmentally relevant polychlorinated biphenyl (PCBs mixture), namely the Fox River mixture, impacts gut microbiome and BA homeostasis. Ninety-day-old adult female conventional (CV) and germ-free (GF) C57BL/6 mice were orally exposed to corn oil (vehicle), or the Fox River mixture at 6 or 30 mg/kg once daily for 3 consecutive days. The PCB low dose profoundly increased BA metabolism related bacteria Akkermansia ( A. ) muciniphila, Clostridium ( C. ) scindens, and Enterococcus in the large intestinal pellet (LIP) of CV mice (16S rRNA sequencing/qPCR). This correlated with a PCB low dose-mediated increase in multiple BAs in serum and small intestinal content (SIP) in a gut microbiota-dependent manner (UPLC-MS/MS). Conversely, at PCB high dose, BA levels remained stable in CV mice correlated with an increase in hepatic efflux transporters and ileal Fgf15. Interestingly, lack of gut microbiota potentiated the PCB-mediated increase in taurine conjugated α and β muricholic acids in liver, SIP, and LIP. Pearson's correlation identified positive correlations between 5 taxa and most secondary BAs. In conclusion, PCBs dose-dependently altered BA homeostasis through a joint effort between host gut-liver axis and intestinal bacteria.